Workload, workplace violence and harassment, and well-being of personal support workers in home and community care - Sayin, Firat; Denton, Margaret; Brookman, Catherine; Davies, Sharon; Zeytinoglu, Isik (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2021)
Demand for home and community care services has continuously increased in Canada and elsewhere in the last few decades due to aging of the population and healthcare policy changes shaped by budgetary limitations. As a result, home and community care organizations are having trouble hiring adequate numbers of healthcare workers to meet the escalating demand, the result being increased workload on these workers. Another stream of literature has shown that care recipients and their family members, frustrated with the limited ability of healthcare workers to provide adequate care because of increased workload, might resort to violence and harassment. Bringing these two streams of literature together, we examined the relationships among three variables : workload ; workplace violence and harassment ; and well-being of personal support workers (PSWs).Using structural equation modeling, we analyzed a 2015 Ontario-wide survey of 1,347 PSWs employed in the home and community care sector. The results indicate that workload is negatively associated with extrinsic and intrinsic job satisfaction, and this relationship is mediated by violence and harassment and by stress. Specifically, workload is positively associated with violence and harassment at work, which in turn is positively associated with stress, which in turn is negatively associated with extrinsic and intrinsic job satisfaction.Our study contributes to the literature by examining the impact of a work environment factor, workload, on the well-being of PSWs. This approach makes it possible to expand the current literature’s focus on psychological processes at the individual level to a more contextual approach. Furthermore, the results have important implications for home and community care organizations as well as for the healthcare sector in general. The well-being of PSWs is critical to retaining them and to ensuring the quality of care they provide their clients. Thus, their workload should be lowered to a more manageable level to help minimize the violence and harassment they experience.